Diagnosis and treatment of spinal cord injury : the neuroscience of spinal cord injury - Rajendram, Rajkumar; Preedy, Victor R.; Martin, Colin R., 1964- (Academic Press, 2022)
Diagnosis and Treatment of Spinal Cord Injury will enhance readers' understanding of the complexities of the diagnosis and management of spinal cord injuries. Featuring chapters on drug delivery, exercise, and rehabilitation, this volume discusses in detail the impact of the clinical features, diagnosis, management, and long-term prognosis of spinal cord injuries on the lives of those affected. The book has applicability for neuroscientists, neurologists, clinicians, and anyone working to better understand spinal cord injuries.